Constipation and risk of cognitive impairment and dementia in adults: a systematic review and meta-analysis - Qiyue Wang; Ting Yi; Xuan Jiang (Frontiers in Neurology)
IntroductionIt has been shown that constipation may have a close association with the occurrence of cognitive impairment (CI). This study was aimed at assessing the risk of CI in patients with constipation and exploring the interactions of constipation with other factors affecting CI.MethodsEmbase, PubMed, Web of Science, and Cochrane were systematically searched to collect relevant literature for assessment of the association between constipation and CI. The included studies was subjected to quality assessment using the NIH quality assessment tool for observational cohort and cross-sectional studies. An odds ratio (OR) was calculated using a random effects model, and subgroup and sensitivity analyses were performed. Publication bias was assessed by the Egger's test and funnel plot, with a P-value of < 0.05 considered to indicate the presence of bias.ResultsA total of 11 studies were included, including five retrospective studies and six cross-sectional studies, with 66,609 participants involved. The OR between constipation and cognitive impairment was 1.11 (95% CI: 1.03–1.20). Subgroup analysis showed that the OR between constipation and CI was 1.33 (95% CI: 1.12–1.58) in patients with Parkinson's disease and 1.05 (95% CI: 0.98–1.13) in patients without Parkinson's disease. The OR was 1.37 (95% CI: 1.07–1.74) in retrospective studies and 1.06 (95% CI: 0.98–1.15) in cross-sectional studies. The OR was 1.29 (95% CI: 0.92–1.80) in Europe and 1.12 (95% CI: 1.04–1.22) in Asia.ConclusionThe risk of CI was 1.11 times higher in constipated patients than in non-constipated patients. Constipation might significantly increase the risk of CI, especially in patients with Parkinson's disease.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025630902, identifier: CRD42025630902.